Generalized fuzzy closed sets in generalized fuzzy topological spaces - Jayasree Chakraborty; Baby Bhattacharya; Arnab Paul (Songklanakarin Journal of Science and Technology (SJST), 2019)
This paper aims to put forward one more difference between generalized topological space and generalized fuzzy topological space via generalized closed set in the respective fields. Also we claim and prove that to a certain extent, the role of generalized closed set in a fuzzy topological space is not similar in nature with that of generalized closed set in a generalized fuzzy topological space. Generalized closed sets coincide with closed sets under some appropriate restrictions though the implication does not hold in general in a generalized fuzzy topological space.